Unknowns as exponents

Find the sum of all possible values for x + y + z x+y+z where x , y , z x,y,z are positive integer such that 2 x + 3 y = z 2 \large{2^x+3^y=z^2}


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Casper Putz
Nov 21, 2017

First note that z z must be odd as 2 x 2^x is even and 3 y 3^y is odd. Using the fact that odd squares are 1 ( m o d 4 ) 1\pmod 4 we get that x = 1 x=1 and y y is odd, or x 2 x\geq 2 and y y is even. If x x is odd then 2 x + 3 y ( 1 ) x 1 z 2 ( m o d 3 ) 2^x + 3^y \equiv (-1)^x\equiv -1 z^2\pmod 3 which gives a contradiction as squares are always 0 0 or 1 1 modulo 3 3 . Hence, x x is even and as x 1 x\neq 1 we also have that y y is even.

Write x = 2 n x = 2n and y = 2 m y = 2m so that ( 2 n ) 2 + ( 2 m ) 2 = z 2 (2^n)^2 + (2^m)^2 = z^2 . Integers a a , b b and c c with the property that a 2 + b 2 = c 2 a^2 + b^2 = c^2 are called Pythagorean triples and we know that every triple ( a , b , c ) (a,b,c) can be written in the form ( s 2 t 2 , 2 s t , s 2 + t 2 ) (s^2-t^2, 2st, s^2+t^2) with s , t N s,t\in\mathbb N . So we can write 2 n = 2 s t 2^n = 2st , 3 m = s 2 t 2 3^m = s^2-t^2 and z = s 2 + t 2 z = s^2+t^2 (note that 2 n 2^n is even and 3 m 3^m is odd so we must have ( a , b ) = ( 3 m , 2 n ) (a,b) = (3^m,2^n) ).

From 2 n = 2 s t 2^n = 2st we get s = 2 k s = 2^k and t = 2 t = 2^\ell for k , N k,\ell\in\mathbb N . As 3 m = 2 2 k 2 2 3^m = 2^{2k} - 2^{2\ell} is even, either k = 0 k = 0 or = 0 \ell = 0 , and because k > k > \ell (otherwise s 2 t 2 < 0 s^2-t^2<0 ) we have = 0 \ell = 0 so t = 1 t = 1 . This means that s = 2 n 1 s = 2^{n-1} . Now we have 3 m = ( 2 n 1 ) 2 1 = ( 2 n 1 1 ) ( 2 n 1 + 1 ) 3^m = (2^{n-1})^2 - 1 = (2^{n-1} - 1)(2^{n-1} + 1) . Both factors have to be powers of 3 3 , but they are not equal modulo 3 3 . So the smallest factor has to be 1 1 so 2 n 1 1 = 1 2^{n-1} - 1 = 1 so n = 2 n = 2 . This gives s = 2 s = 2 and so m = 1 m = 1 and z = 5 z = 5 . Hence, the only solution is x = 4 x = 4 , y = 2 y = 2 and z = 5 z = 5 so the sum is 4 + 2 + 5 = 11 4+2+5 = 11 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...